MULTILINGUALISM IN THE MODERN TAJIK PRESS - E.K. Molchanova (Многоязычие в образовательном пространстве)
The article analyses the content, form and vocabulary of the modern Tajik press. Its multilingualism is noted based on the following sources: updating of vocabulary, original and Arabic (mainly religious), considered obsolete in the 20th century, as well as Russianisms, Persianisms, and internationalisms. The study is based on new material and is therefore relevant. The author uses a descriptive method taking into account the theory of language contacts. This allows one to get a concrete idea of the current state of the Tajik media